Patrones de actividad de dos morfos de coloración de la vulnerable güiña, Leopardus guigna (Molina, 1872), en bosques templados del sur de Chile - Hernández, Felipe; Gálvez, Nicolás; Gimona, Alessandro; Laker, Jerry; Bonacic, Cristián (Gayana, 2015)
Here we provide the first analysis of activity patterns exhibited by spotted and melanistic colour morphs of the vulnerable guiña Leopardus guigna, in a forest landscape of southern Chile. Camera traps showed guiñas were mainly active at night (64% of photos). Melanistic guiñas were more nocturnal (82% of photos) than the more common spotted cats (57%). Spotted guiñas were more active on cloudy and moonless nights. Our study provides novel findings about the behavioural plasticity of guiña in different ambient conditions, and the relative advantage to each colour morph to persist in an increasingly human-dominated landscape.